The curse of the mummy's tomb - Stine, R. L. (New York : Scholastic, 2009)
Gabe loses track of his cousin Sari in a pyramid and begins to wonder if the curse of the mummy's tomb is real.
"Now with bonus features"--Cover.
4.0
5-8
Keywords: Mummies -- Juvenile fiction; Pyramids -- Juvenile fiction; Horror stories; Mummies -- Fiction; Pyramids -- Fiction; Horror fiction; Mummies -- Fiction; Pyramids -- Fiction